A Hierarchical Approach to Realignment Strategies in Adult Cervical Deformity Surgery. Issue 3 (13th April 2023) - Williamson, Tyler K.; Lebovic, Jordan; Schoenfeld, Andrew J.; Imbo, Bailey; Joujon-Roche, Rachel; Tretiakov, Peter; Krol, Oscar; Bennett-Caso, Claudia; Owusu-Sarpong, Stephane; Dave, Pooja; McFarland, Kimberly; Mir, Jamshaid; et al.
Abstract : Study Design: Retrospective cohort study. Objective: Construct an individualized cervical realignment strategy based on patient parameters at the presentation that results in superior 2-year health-related quality of life metrics and decreased rates of junctional failure and reoperation following adult cervical deformity surgery. Summary of Background Data: Research has previously focused on adult cervical deformity realignment thresholds for maximizing clinical outcomes while minimizing complications. However, realignment strategies may differ based on patient presentation and clinical characteristics. Methods: We included adult cervical deformity patients with 2-year data. The optimal outcome was defined as meeting good clinical outcomes without distal junctional failure or reoperation. Radiographic parameters assessed included C2 Slope, C2–C7, McGregor's slope, TS–CL, cSVA, T1 slope, and preoperative lowest-instrumented vertebra (LIV) inclination angle. Conditional inference trees were used to establish thresholds for each parameter based on achieving the optimal outcome. Analysis of Covariance and multivariable logistic regression analysis, controlling for age, comorbidities, baseline deformity and disability, and surgical factors, assessed outcome rates for the hierarchical approach within each deformity group. Results: One hundred twenty-seven patients were included. After correction, there was a significant difference in meeting the optimal outcome when correcting the C2 slope below 10 degrees (85% vs. 34%, P <0.001), along with lower rates of distal junctional failure (DJF) (7% vs. 42%, P <0.001). Next, after isolating patients below the C2 slope threshold, the selection of LIV with an inclination between 0 and 40 degrees demonstrated lower rates of distal junctional kyphosis and higher odds of meeting optimal outcome(OR: 4.2, P =0.011). The best third step was the correction of cSVA below 35 mm. This hierarchical approach (11% of the cohort) led to significantly lower rates of DJF (0% vs. 15%, P <0.007), reoperation (8% vs. 28%, P <0.001), and higher rates of meeting optimal outcome (93% vs. 36%, P <0.001) when controlling for age, comorbidities, and baseline deformity and disability. Conclusion: Our results indicate that the correction of C2 slope should be prioritized during cervical deformity surgery, with the selection of a stable LIV and correction of cervical SVA below the idealized threshold. Among the numerous radiographic parameters considered during preoperative planning for cervical deformity correction, our determinations help surgeons prioritize those realignment strategies that maximize the health-related quality of life outcomes and minimize complications. Level of Evidence: Level—III.